Influence of Additional Strut Elements in 3D Re-Entrant Auxetic Unit Cells on the Damage and Energy Absorption Properties - Kaya, A. C.; Korucu, A.; Bogoclu, M. (SPRINGER, 2024)
Background Geometric parameter optimization, novel design, and mechanism modeling of auxetic materials have been widely studied. However, manipulating the topology of the 3d printed auxetic unit cells and its influence on the damage have yet to be explored. Objective This study aims to characterize the energy absorption properties and damage mechanisms of the modified auxetic unit cells. Methods In the current study, bending-dominated re-entrant auxetic unit cells (Cell0), torsion-dominated auxetic unit cells with cross elements (CellX), buckling-dominated auxetic unit cells with vertical elements (CellB), and bending-dominated auxetic unit cells with panels (CellW) have been fabricated by FDM (Fused deposition modeling). Uniaxial compression testing of the PLA (Polylactic acid) unit cells has been carried out, and a camera has observed their deformation behavior. SR- mu CT (Synchrotron radiation microtomography) and an SEM (Secondary electron microscope) accomplished further damage analysis of the struts. Results Adding additional struts hinders the lateral shrinking of the re-entrant auxetics, and re-entrant auxetic unit cells with cross elements have shown higher energy absorption capacity and efficiency than others. The struts' damage has been governed by building direction, printed material, and strut dimensions. Intra-layer and interlayer fracture of the layers and rupture in the circumferential direction of the PLA struts have been observed in the SR- mu CT slices. Conclusions By additional struts, it is possible to fabricate complex auxetic structures with enhanced energy absorption properties, but their inherent characteristics dominate the damage of the struts in the auxetic unit cells.
Keywords: Auxetic materials; Negative poisson's ratio; Compression test; PLA; FOAMS; DEFORMATION; Materials Science; Mechanics